Diseño de una blonda a partir del aprovechamiento de almidón de yuca. Villavicencio-Meta. - Murillo Lopez, David Leonardo; Gutierrez Herrera, Diego Alexander (Universidad Antonio Nariño, 2021)
The department of Meta is one of the largest cassava producers in Colombia, highlighting one of the great properties of sweet cassava, which has a high percentage of glucose, achieving exceptional flexibility and hardness to generate an alternative to excessive demand for single-use expanded polystyrene such as doilies; This is why the Design of a lace was generated from the use of cassava starch. For the development of this research, 4 stages were proposed; Initially, we started with a base composition as a result of a documentary search to carry out what would be the obtaining of a biopolymer, describing the step-by-step for obtaining it. This procedure was carried out in a laboratory report. After obtaining the biopolymer, a matrix was proposed with the results of 20 tests in which the components were modified, highlighting in the drying process the% of humidity obtained in the shortest time, from this laboratory practice it was determined that 2 different types of composition that managed to have a humidity of 25% in the shortest time 3 models of different dimensions of each composition were established, the samples were analyzed for flexural properties, humidity, hardness and density to obtain a 70/30 composition of the starch cassava versus fiber reinforcement fique. Finally, a cost table was made to know the total cost of obtaining each of the 3 lace models (15cm, 20cm and 25cm) and to generate a competitive alternative option for the plastics industry to reduce the excessive use of polystyrene. expanded single use, making a great contribution to the decontamination of the planet.